Analisis Pengaruh Green Marketing dan Networking Capability terhadap Kinerja Pemasaran UKM Batik di Indonesia - Vita Dhameria (Portofolio: Jurnal Ekonomi, Bisnis, Manajemen, dan Akuntansi, 2026)
The purpose of this study is to examine how networking skills and green marketing affect marketing performance in Indonesian batik SMEs using green trust as an intervening variable. The study uses an explanatory research design and a quantitative methodology. 120 respondents made up the sample, which was chosen using purposive sampling and included batik SME actors who have adopted eco-friendly practices. Structural Equation Modeling (SEM) using AMOS 22 was used to analyze the data. The findings show that green trust is positively and significantly impacted by green marketing and networking skills. While green marketing has no discernible direct impact on marketing performance, networking capabilities also significantly and favorably influence marketing performance. Additionally, green trust has a major impact on marketing effectiveness and functions as a mediating factor in the link between networking capability and green marketing. These results imply that enhancing business networks and fostering customer trust are more efficient ways to improve the marketing performance of batik SMEs. To establish a sustained competitive advantage, it is crucial to combine green marketing techniques with initiatives to improve credibility and commercial partnerships.